Analysis of the digital marketing strategy of anak hebat Indonesia publisher through Instagram - Siswanto, Andi Siswanto (Universitas Ahmad Dahlan, 2022)
This study aims to determine the digital marketing strategy on Instagram social media used by the publisher Anak Hebat Indonesia (AHI) and to find out why there is an increasing interest in buying books amid the phenomenon of low interest in reading in Indonesia. This research was carried out in october-december 2021. This research is a qualitative research with a case study approach on the Instagram social media publisher Anak Hebat Indonesia (AHI). The results of this research show that the digital marketing strategy used by AHI publishers through Instagram has been effective, in terms of the cost of advertising, it can be seen from the increasing number of visitors. Good interaction with Minah's Instagram admin in responding friendly and like a friend, related to books and others. Incentive programs have also been created and implemented well, including a giveaway program on Friday blessing, product discounts when purchasing on Instagram, and interesting book titles. And for the appearance of instagram @ penerbitahi official, it is good and informative in conveying the meaning of the message or information, so that followers can easily understand it and are comfortable to see with pastel post colors. The phenomenon of buying books is quite high but reading levels are low in Indonesia, it can be concluded that consumers buy books because they are not only read, but there are also those who are just collectors of the book, because of the cool book cover design, as well as the very title of the book. interesting, and because of the discount from normal days.